EO-based mouthwashes: Is there something that should be known? - Marinković Jelena; Rakašević Dragana; Nemoda Milica; Nikolić Biljana; Marković Tatjana; Matijević Stevo; Marković Dejan (Balkan Stomatological Society, 2023)
The possibility to utilize the antibacterial and antibiofilm potential of essential oils (EOs) in dentistry is recognized and best seen in the design of EO-based mouthwashes. The up-to-date results, obtained with the most commonly used formulation being consisted of thymol, eucalyptol, menthol, and methyl salicylate (Listerine), proved its efficacy against plaque and gingival inflammation. However, novel alcohol-free products remain to be further investigated. Commercially available mouthwash containing curcumin, clove oil, mentha oil, eucalyptol, thymol and tea tree oil, and the mouthwash based on ginger EO (a-zingiberene, b-bisabolene, b-sesquiphellandrene, curcumene), reduced plaque index and improved periodontal status of the patients. The plaque index was also reduced and overall healing was improved after the surgical removal of the third molar by mouthwash containing John wort oil. In addition, Cinnamomum zeylanicum EO-based mouthwash and mouthwash containing peppermint oil were efficient against stomatitis and xerostomia, respectively. In addition to beneficial effects achieved in the mouth, i.e. at the appropriate site of application, novel investigations pointed-out that EO-based mouthwashes could be recognized as efficient in the reduction of bacterial and viral aerosols. This has been shown for Listerine, and for several mouthwashes containing following active substances of plants' EO origin: a-farnesene, b-farnesene, farnesol, nerolidol, a-bulnesene, eremanthin, b-sesquiphellandrene, spiroether, cinnamylacetate, cinnamaldehyde, eugenol, menthol, and carvacrol. This finding could be of special interest, in order to be included in further clinical studies related to COVID -19 pandemic.